Skeletal Muscle Involvement Pattern of Hereditary Transthyretin Amyloidosis: A Study Based on Muscle MRI - Chu, Xujun; Du, Kang; Tang, Yuwei; Zhao, Xutong; Yu, Meng; Zheng, Yiming; Deng, Jianwen; Lv, He; Zhang, Wei; Wang, Zhaoxia; Yuan, Yun; Meng, Lingchao (Frontiers in Neurology, 2022)
Objects This study was intended to explore the characteristics of muscle magnetic resonance imaging (MRI) of patients with hereditary transthyretin amyloidosis (ATTRv amyloidosis) prospectively. Methods The clinical data of 20 patients with ATTRv amyloidosis at our hospital between July 2020 and August 2021 were analyzed. MRI of lower limbs including calf muscles was performed in all these 20 patients and MRI of thigh muscles was performed in 16 of them. Results The mean age of the 20 patients with ATTRv amyloidosis was 44.2 years (ranging from 26 to 60) whose mean duration of weakness was 23.3 ± 23.0 (ranging from 0 to 84) months. All the patients presented with polyneuropathy, and 18 of them with weakness in their lower limbs. Muscle involvement was selective in these patients with ATTRv amyloidosis. The posterior group of muscles was heavily fatty, and the soleus muscle was the most heavily involved. The proportion of fatty infiltration scores at the calf level was higher than at the thigh level with paired comparison for most patients. Three of these patients had more severely fatty infiltration of muscles at the thigh level. The fatty infiltration of posterior compartments at the calf level was highly consistent with neuropathy impairment scores of lower limbs (weakness), the strength of ankle plantar flexion muscles, and the amplitude of the compound muscle action potential of the tibial nerve. Conclusions It was found that the pattern of muscle fatty infiltration was consistent with a distal-to-proximal gradient on the whole and that proximal involvements in MRI of lower limbs in some patients could also be observed. Selective fatty infiltration of muscles of posterior compartments and fatty infiltration of the soleus muscle might be typical of ATTRv amyloidosis.